2014
DOI: 10.1177/2167696814561544
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Siblings and Psychological Needs in Predicting Life Satisfaction During Emerging Adulthood

Abstract: Life satisfaction during emerging adulthood is important because it promotes positive psychological functioning and prevents risky behaviors that lead to poor health. Self-determination theory emphasizes the agentic nature of individuals to maintain well-being through the psychological needs of autonomy, competence, and relatedness, and the social contexts which influence these processes. Because siblings serve as an emotional resource throughout the life span, sibling support may predict well-being through th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
51
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(57 citation statements)
references
References 49 publications
1
51
0
2
Order By: Relevance
“…Adolescents who perceive general closeness and academic support from siblings are more likely to report positive school attitudes and high academic motivation (Alfaro & Umaña-Taylor, 2010; Milevsky & Levitt, 2005). In addition, experiencing support from a sibling is associated with later feelings of competence, autonomy, and relatedness during adolescence, as well as life satisfaction during the transition into emerging adulthood (Hollifield & Conger, 2015). Further, in the face of stressful life events, perceived affection and closeness from a sibling can buffer against the progression of internalizing behaviors across adolescence (Buist et al, 2014; Gass, Jenkins, & Dunn, 2007).…”
Section: Social Influence On Positive Youth Developmentmentioning
confidence: 99%
“…Adolescents who perceive general closeness and academic support from siblings are more likely to report positive school attitudes and high academic motivation (Alfaro & Umaña-Taylor, 2010; Milevsky & Levitt, 2005). In addition, experiencing support from a sibling is associated with later feelings of competence, autonomy, and relatedness during adolescence, as well as life satisfaction during the transition into emerging adulthood (Hollifield & Conger, 2015). Further, in the face of stressful life events, perceived affection and closeness from a sibling can buffer against the progression of internalizing behaviors across adolescence (Buist et al, 2014; Gass, Jenkins, & Dunn, 2007).…”
Section: Social Influence On Positive Youth Developmentmentioning
confidence: 99%
“…Supportive sibling relationships during adolescence are associated with facets of adjustment such as greater concurrent self‐concept, sense of autonomy, and self‐esteem, as well as subsequent self‐esteem and positive peer relationships (Branje et al., ; Dailey, ; Yeh & Lempers, ). Additionally, longitudinal work has found that perceptions of sibling support during adolescence positively predict competence, autonomy, connectedness with siblings, and life satisfaction above and beyond sibling structural characteristics such as dyad sex and birth order (Hollifield & Conger, ; Milevsky & Levitt, ). Given the positive association between supportive sibling relationships and healthy self‐perceptions and well‐being, which is consistent with the framework of RRT, sibling relationships may also correlate with adolescent school commitment through these processes.…”
Section: Sibling Relationships As a Source Of Supportmentioning
confidence: 99%
“…Older siblings provide more modeling, advice, support, and knowledge to their younger siblings than vice versa due to their greater power, authority, experience, and access to resources (Bandura, ; Hollifield & Conger, ; Tucker, Barber, & Eccles, ). Tucker et al.…”
Section: Sibling Relationships As a Source Of Supportmentioning
confidence: 99%
See 2 more Smart Citations